KAJIAN HASIL PENELITIAN EMPIRIS HUBUNGAN KINERJA KEUANGAN, STRATEGI INOVASI, BIAYA MODAL DAN KINERJA PASAR TERHADAP CORPORATE SOCIAL PERFORMANCE - Pujiningsih, Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
This article aims to review empirical research results of corporate social performance (CSP) themes. This article will discuss, firstly, the relationship of financial performance and CSP, the relationships of both are negative, positive and no correlation, based on difference theories. Secondly, the correlation of innovation strategy and CSP are explained by signaling theory. Thirdly, the correlation of cost of capital and CSP can be illuminated by good management theory. Fourth, correlation of market performance and CSP can be explained by signaling and good management theory. The advantages of this article can guide researchers to developed theoretical framework and hypothesis.